Social origin and the intention to enrol in higher education: personality traits as a mechanism of reproduction or mobility? - Nika, David; Grüttner, Michael; Buchholz, Sandra (Frontiers in Sociology, 2025)
A vast amount of research has shown that social inequality in educational attainment is a persistent phenomenon. Sociological research explains unequal educational decisions via primary and secondary effects of social origin, respectively unequal school performance and patterns of educational decision-making. So far, educational sociology has largely ignored the role of personality traits for educational decision-making. Therefore, we extend the sociological perspective on primary and secondary effects of social origin to include personality traits as non-cognitive resources. Three plausible mechanisms could be at work: (1) For students from low social origins, favourable personality traits could compensate for the lack of other important resources and be more important for their study intention (resource substitution). (2) Although students from low social origins benefit most from personal traits, they lack precisely these personal resources (structural amplification). (3) Students from high social origins have more favourable personality traits and can also profit more from them (resource multiplication). Using data from the DZHW Panel Study of School Leavers with a Higher Education Entrance Qualification, we estimate a structural equation model (SEM) to examine the direct, indirect, and total effects of personality traits on the intention to enrol in higher education. Results are twofold: First, personality traits are significant determinants of primary and secondary effects of social origin. Second and most importantly, openness proves to be a key resource: while students from less advantaged social origin generally display lower levels of openness, this group benefits most from this trait in forming their intention to pursue higher education—a pattern consistent with structural amplification. These results highlight the dual role of personality traits in both enabling individual upward mobility and contributing to the persistence of social inequality. The study underscores the importance of considering non-cognitive resources in explanations of educational inequality and points to potential interventions aimed at fostering openness.